ANALISIS INTERKULTURAL TUTURAN BAHASA JERMAN DALAM BUKU AJAR DI PERGURUAN TINGGI - Sudarmaji -; Pratomo Widodo (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to identify intercultural utterances in German course books for higher education. The data sources were German course books, namely Studio d A1, A2, and B2 as primary course books. The data were collected through marked listening and reading techniques. They were analyzed by means of content analysis and extralingual correspondence. The findings are as follows. First, the intercultural themes are relatedto food, clothing, jobs, marriage systems, perceptions of time, politeness, traditions, regulations, and languages. Second, the factors causing differences include seasons, staple foods, ideologies (religions), language systems, welfare levels, and nations’ histories. Third, the factor of understanding of the German culture is an important foundation tounderstand intercultural utterances.